ASEAN AND THE CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES: USING INTERNATIONAL LAW TO PROMOTE SOCIAL AND ECONOMIC DEVELOPMENT - Petersen, Carole (Indonesian Journal of International Law, 2012)
This paper examines the potential impact within ASEAN of the Convention on the Rights of Persons with Disabilities (CRPD). Although persons with disabilities should also enjoy the rights provided in previous human rights instruments, a specialist treaty is necessary because many individuals with disabilities are still marginalized, with low rates of education and employment. States parties are thus obligated to remove physical and attitudinal barriers and to actively promote capability and inclusion of all persons with disabilities. Disability rights organizations have urged members of ASEAN to ratify the CRPD. At present, Laos, Malaysia, Philippines, and Thailand are states parties and the Indonesian House of Representatives voted to ratify the treaty in October 2011. Full ratification would build upon progress made during the Asian and Pacific Decade of Disabled Persons, which led to the adoption of the Biwako Millennium Framework For Action Towards an Inclusive, Barrier Free and Rights-Based Society for Persons with a Disability in Asia and the Pacific. Ratification of the CRPD should strengthen governments’ efforts to implement the Biwako Millennium Framework because all states parties to the CRPD are obligated to report periodically to the United Nations Committee on the Rights of Persons with Disabilities. This is therefore an opportune time to analyze what the treaty could mean for persons with disabilities in ASEAN.